2022
DOI: 10.1097/aud.0000000000001315
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Cognitive Decline Associated With Hearing Loss and Bilateral Vestibulopathy: Insights From a Prospective Cross-Sectional Study Using the Repeatable Battery for the Assessment of Neuropsychological Status Adjusted for the Hearing Impaired in the DFNA9 Population

Abstract: Background: DeaFNess Autosomal dominant 9 (DFNA9) is a hereditary disorder known to affect both hearing and vestibular function in its carriers. Its phenotype is characterized by progressive sensorineural hearing loss (SNHL) and vestibular dysfunction evolving towards bilateral vestibulopathy (BV) by the 3rd to 5th life decade. Recent studies have identified the impact of hearing loss and vestibular dysfunction on cognitive functioning. Objective: The main objective of this study was to investigate how the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…Most of the patient group with HL comprised persons with a heterozygous dominant-negative COCH gene variant, causing DFNA9 (53%) . This disorder has a progressive sensorineural HL and vestibular dysfunction that eventually evolves toward BV . Eighty-three percent of the participants with BV with NH had an idiopathic BV, often with a sudden onset.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patient group with HL comprised persons with a heterozygous dominant-negative COCH gene variant, causing DFNA9 (53%) . This disorder has a progressive sensorineural HL and vestibular dysfunction that eventually evolves toward BV . Eighty-three percent of the participants with BV with NH had an idiopathic BV, often with a sudden onset.…”
Section: Discussionmentioning
confidence: 99%
“…The responsiveness of the RBANS-H will allow the establishment of a cognitive trajectory in a population with an inevitable evolution towards SNHL and BV, and possibly also dementia due to its increased risk for it and accelerated cognitive decline observed in this population 27…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, homozygous loss-of-function mutations in COCH lead to autosomal recessive, early-onset, severe SNHL (DFNB110) 21 26. A recent cross-sectional study from Gommeren et al 27 found significantly worse results in patients with DFNA9 in cognitive performance compared with a cognitively healthy control group. This highlights the need for adequate treatment to prevent further cognitive decline and reduce dementia risk in this population.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicates that hearing loss is correlated with poorer scores on both the immediate memory and language subscales, as well as the total RBANS-H scale. Conversely, vestibular loss was found to be associated with reduced performance on the attention subscale of the RBANS-H ( 26 ).…”
Section: Discussionmentioning
confidence: 99%